Does Education Level Mitigate the Effect of Poverty on Total Knee Arthroplasty Outcomes?. Issue 6 (12th April 2018) - Goodman, Susan M.; Mandl, Lisa A.; Mehta, Bella; Navarro‐Millan, Iris; Russell, Linda A.; Parks, Michael L.; Dey, Shirin A.; Crego, Daisy; Figgie, Mark P.; Nguyen, Joseph T.; Szymonifka, Jackie; Zhang, Meng; et al.
Abstract : Objective: Total knee arthroplasty (TKA) outcomes are worse for patients from poor neighborhoods, but whether education mitigates the effect of poverty is not known. We assessed the interaction between education and poverty on 2‐year Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain and function. Methods: Patient‐level variables from an institutional registry were linked to US Census Bureau data (census tract [CT] level). Statistical models including patient and CT‐level variables were constructed within multilevel frameworks. Linear mixed‐effects models with separate random intercepts for each CT were used to assess the interaction between education and poverty at the individual and community level on WOMAC scores. Results: Of 3, 970 TKA patients, 2, 438 (61%) had some college or more. Having no college was associated with worse pain and function at baseline and 2 years ( P = 0.0001). Living in a poor neighborhood (>20% below poverty line) was associated with worse 2‐year pain ( P = 0.02) and function ( P = 0.006). There was a strong interaction between individual education and community poverty with WOMAC scores at 2 years. Patients without college living in poor communities had pain scores that were 10 points worse than those with some college (83.4% versus 75.7%; P < 0.0001); in wealthy communities, college was associated with a 1‐point difference in pain. Function was similar. Conclusion: In poor communities, those without college attain 2‐year WOMAC scores that are 10 points worse than those with some college; education has no impact on TKA outcomes in wealthy communities. How education protects those in impoverished communities warrants further study.